Tier II Interventions within the Framework of School-Wide Positive Behavior Support: Essential Features for Design, Implementation, and Maintenance - Anderson, Cynthia M. (Springer International Publishing, 2010)
To meet the complex social behavioral and academic needs of all students, schools benefit from having available multiple evidence-based interventions of varying intensity. School-wide positive behavior support provides a framework within which a continuum of evidence-based interventions can be implemented in a school. This framework includes three levels or tiers of intervention; Tier I (primary or universal), Tier II (secondary or targeted), and Tier III (tertiary or individualized) supports. In this paper we review the logic behind school-wide positive behavior support and then focus on Tier II interventions, as this level of support has received the least attention in the literature. We delineate the key features of Tier II interventions as implemented within school-wide positive behavior support, provide guidelines for matching Tier II interventions to school and student needs, and describe how schools plan for implementation and maintenance of selected interventions.